Real-time observation and quantification of carbon black oxidation in an environmental transmission electron microscope: Impact of particle size and electron beam. (30th April 2022) - Dadsetan, Mehran; Naseri, Ali; Thomson, Murray J.
Abstract: Carbon black oxidation is a post-treatment method to control its properties for different applications, and its outcomes may depend on the particle size. Three different sizes of carbon blacks were oxidized in an environmental transmission electron microscope to study the size effect on their oxidation pathway and rate. The oxidation at the nanoscale has been quantified using the ASTM D3849-14a standard method for the carbon blacks and compared with the theory of solid particle burning, i.e., D 2 law. This comparison confirms the validity of the diffusion-controlled burning model for all three samples oxidized at 800°C in the presence of oxygen molecules. Electron microscope images show surface burning is the governing mode under this condition. Oxidation under electron-beam irradiation shows that the oxidation rate reduces by ∼0%, 30%, and 80% for particles with 33, 112, and 356 nm in diameter, respectively. The results suggest that the electron beam is causing the atomic bonds to break and transform to the graphitic structure at relatively high temperatures (e.g., 800°C) that causes oxidation rate reduction in larger particles. Despite the reduction in oxidation rate as the initial size of carbon particles increases, observations show that surface burning is the dominant mode under electron-beam irradiation. Graphical abstract: Image 1 Highlights: All particles between 33 to 365 nm show surface burning under beam-off and –on conditions. Oxidation in the presence of molecular oxygen follows the theory of solid particle burning, i.e., D 2  law. By increasing initial particle size, oxidation in the presence of the beam and oxygen molecules deviates from the theory.